The interplay between DNA topology and accessory factors in site-specific recombination in bacteria and their bacteriophages. (1st December 2016) - Dorman, Charles; Bogue, Marina
Site-specific recombination is employed widely in bacteria and bacteriophage as a basis for genetic switching events that control phenotypic variation. It plays a vital role in the life cycles of phages and in the replication cycles of chromosomes and plasmids in bacteria. Site-specific recombinases drive these processes using very short segments of identical (or nearly identical) DNA sequences. In some cases, the efficiencies of the recombination reactions are modulated by the topological state of the participating DNA sequences and by the availability of accessory proteins that shape the DNA. These dependencies link the molecular machines that conduct the recombination reactions to the physiological state of the cell. This is because the topological state of bacterial DNA varies constantly during the growth cycle and so does the availability of the accessory factors. In addition, some accessory factors are under allosteric control by metabolic products or second messengers that report the physiological status of the cell. The interplay between DNA topology, accessory factors and site-specific recombination provides a powerful illustration of the connectedness and integration of molecular events in bacterial cells and in viruses that parasitise bacterial cells.